Faktor Yang Berhubungan dengan Kecelakaan Kerja Pada Pekerja Bangunan di Desa Telago Biru Kecamatan Siulak - Gilang Septi Yulian; Putri Sahara Harahap; Renny Listiawaty (Jurnal Dunia Kesmas, 2022)
A work accident is an unwanted and unexpected event that can cause loss of time, property, or loss of life. The construction sector is an area with a fairly high risk of work accidents. Work accidents include slipping, being scratched by a sharp object, hitting the head with a heavy object, falling from a height, feet stuck with nails. Talago Biru Village is currently undergoing development development. The purpose of this study was to determine the factors associated with work accidents on construction workers in Telago Biru Village, Siulak District, Kerinci Regency. This research is a quantitative research using a cross sectional design. The study was conducted in Telago Biru, Siulak District, from April 18 to May 14, 2022. The sample of the research was construction workers in Telago Biru Village, Siulak District, amounting to 47 people. The sampling technique used was total sampling technique. The research instrument is a questionnaire. Data were analyzed using chi square statistical test. As many as 61.7% of respondents had experienced work accidents, 55.3% of respondents worked with fatigue category, 46.8% of respondents worked with unfavorable actions and 46.8% of respondents worked with unfavorable working conditions. The results of the bivariate analysis showed that there was a relationship between work fatigue (p = 0.007), unsafe acts (p = 0.000) and unsafe conditions (p = 0.018) with work accidents on construction workers in Telago Biru Village, Siulak District, Kerinci Regency.